Ground beetles as bioregulators of harmful insect populations on arable land - Popović Aleksandra; Petrović Miloš; Šućur Jovana; Petrović Aleksandra; Bursić Vojislava; Ivanović Ivana; International Symposium on Analytical and Environmental Problems (21.) (2015) (Szeged) (2015)
Ground beetles are the typical polyphagous predators, very important for the maintenance of agroecosystems and other ecosystems, therefore often the subject of research. The aim of this study is to determine the adults of the family of ground beetles. Moreover, the dominance and degree of faunal similarity of ground beetles were observed. During research in the fields of wheat, maize and sugar beet on the territory of Vojvodina on de fields of Bečej and Rimski Šančevi, using the method of "Barber traps" a total of 1,519 individuals of the ground beetles family were collected. The dominant species in the three above-mentioned crops and at all three sites were predators in the genera of Pterostichus spp., Harpalus spp. and Anchomenus spp. Furthermore, based on the obtained results it can be concluded that the composition of ground beetles is dependent on the ruling biotic and abiotic factors, and the combination of these factors creates a specific micro climate conditions, thus the characteristic fauna.